Faktor-faktor yang Memengaruhi Keputusan Petani Mengikuti Program Asuransi Usahatani Padi (AUTP) di Kecamatan Gabus Kabupaten Pati - Kurniawati, Hesti; Mukson, Mukson; Mariyono, Joko (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyze the implementation of the Rice Farming Insurance Program (AUTP), describe the characteristics of AUTP participants, and examine the factors influencing farmers' decisions to participate in the program in Gabus District, Pati Regency. The research employed a survey method and was conducted from February to March 2025. A total of 180 samples were collected, comprising 126 farmers who participated in AUTP and 54 who did not, selected using a disproportionate stratified random sampling technique. Data analysis utilized both descriptive and quantitative methods, specifically binary logistic regression. The findings indicate that 1The number of AUTP participants in Gabus District for the years 2022, 2023, and 2024 were 595, 1,213, and 548 respectively, accounting for 21.6% of the total AUTP participants in Pati Regency in 2024. Claim payments amounted to IDR 861,960,000 in 2022 and IDR 40,800,000 in 2023. 2) Factors influencing farmers' decisions to participate in AUTP simultaneously include age, education, land area, farming experience, number of family dependents, knowledge about AUTP, extension agent activity level, and access to the AUTP program. Partially, the significant factors are the number of family dependents, knowledge about AUTP, and the activity level of extension agents.